Study of mapping relationship between surface micro–defect and haze of polycarbonate plate. (1st January 2015) - Huang, Yao; Wu, Daming; Meng, Qingyun
This paper investigates the mapping relationship between surface micro–defects and haze of polycarbonate (PC) plate. Experiment studies showed that the PC plate with different degree of surface micro–defect can be produced by the process of injection and hot embossing, and then the haze of the PC plate can be measured by haze tester. Simulation studies were made through ray tracing method to find the proper topography function of the surface of the plate and calculate the haze of the plate, so as to study the relationship between surface micro–defect and haze. Finally, it was found that the experimental results validated the theoretical simulation well. And the prediction and evaluation of the haze through the mapping relationship was available.